Teori Nasakh Mansukh Dalam Penetapan Hukum Syariat Islam - Muhammad Husni dan Fathul Wahab (STIT Muhammadiyah Paciran Lamongan, 2020)
he existence of nasakh and mansukh in the determination of Islamiclaw is very important, because not always the law in one place is the same as theplace and conditions in other places. It's just that in imposing nasakh andmansukh this is limited to the problems of shar'i law, while other than that it is notpermissible such as the issue of aqidah or the points of worship and moralprinciples, such as justice, honesty, prohibition of shirk, killing, stealing andothers etc .. Besides that, the determination of nasakh and mansukh is notpermitted by using ijtihad or the opinions of the scholars, but it is indeed purefrom Allah Almighty contained in the Qur'an. However, there are two opposinggroups namely those who support the existence of nasakh and mansukh in theQur'an and groups who reject the existence of nasakh and mansukh in the Qur'an.The middle way taken is to compromise the two opposing groups by reviewing theterms understanding nasakh and mansukh. With this compromise, it is hoped thatthere will be no more opposition regarding nasakh and mansukh. For this reasonthe scholars set ways to know nasakh and mansukh strictly. Despite the pros andcons of nasakh and mansukh. Nasakh and mansukh have provided great lessonsfor Muslims including the development of tasyri 'towards the level and the desirefor goodness and convenience for Muslims.